2005
DOI: 10.1021/jp053273v
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of the Adsorption of Alkanethiols on Cu(111), Ag(111), and Au(111) in the Low and High Coverage Regimes

Abstract: The structure, the surface bonding, and the energetics of alkanethiols adsorbed on Cu(111), Ag(111), and Au(111) surfaces were studied under low and high coverages. The potential energy surfaces (PES) for the thiol/metal interaction were investigated in the absence and presence of externally applied electric fields in order to simulate the effect of the electrode potential on the surface bonding. The electric field affects the corrugation of the PES which decreases for negative fields and increases for positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
170
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(220 citation statements)
references
References 39 publications
41
170
2
1
Order By: Relevance
“…Cometto et al [67]; interestingly, these authors also found that the total energy of this Au-adatom-thiolate moiety was also most identical in the fcc and hcp hollow sites, and that the barrier to diffusion between these sites is very low, consistent with facile diffusion at room temperature between these sites. This result provides a rationale for the facile interchange of the (√3x√3) At this point it is appropriate to summarise the main conclusions regarding the simplest system, Au(111)/methylthiolate, which has been investigated in detail only at low coverage (by STM) and in the 0.33 ML ordered (√3x√3), phase as described above.…”
Section: Specifically Morikawa Et Almentioning
confidence: 81%
“…Cometto et al [67]; interestingly, these authors also found that the total energy of this Au-adatom-thiolate moiety was also most identical in the fcc and hcp hollow sites, and that the barrier to diffusion between these sites is very low, consistent with facile diffusion at room temperature between these sites. This result provides a rationale for the facile interchange of the (√3x√3) At this point it is appropriate to summarise the main conclusions regarding the simplest system, Au(111)/methylthiolate, which has been investigated in detail only at low coverage (by STM) and in the 0.33 ML ordered (√3x√3), phase as described above.…”
Section: Specifically Morikawa Et Almentioning
confidence: 81%
“…[20][21][22][23][24][25][26][27] Recently a density functional theory study was performed to investigate the adsorption of alkanethiols on Cu, Ag, and Au surfaces, predicting dissimilar ionic characteristics depending on the metal substrates. 28 Solvent dependent charge transfer of the ruthenium bipyridine (Ru-bpy) dye on colloidal Ag and Au surface has been recently reported by means of SERS. 29 Although quite a few studies have explored the different adsorption structures of SAMs on metal surfaces, [20][21][22][23][24][25][26][27][28] no reports have investigated ruthenium bipyridine (Ru-bpy) dye on metal surfaces using potential dependent vibrational spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The relative stabilities suggest that the interface consists of MeS-Au-MeS complexes. Several alternative structures have been proposed during recent years [15][16][17][18][19] of which some are preferred over the traditional model but not over the structure with methyl thiolate complexes ͓Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14] This configuration is, however, predicted to be unstable with respect to surface reconstruction with RS adsorbed at defects 15,16 or adatoms. [17][18][19][20][21] Among the different suggestions, one that comprises two RS-Au-RS units in each c͑4 ϫ 2͒ supercell is predicted to be energetically favored. 22 Although there is an uncertainty concerning the ability of state-of-the-art DFT methods to predict small energy differences ͓in particular, for reconstructed RS / Au͑111͒ systems, as the cohesive energy of gold is underestimated by ϳ15%͔ the structure based on RS-Au-RS units is consistent with the bulk of experimental data.…”
Section: Introductionmentioning
confidence: 99%